2009
DOI: 10.1111/j.1440-1797.2009.01108.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine‐induced heat shock protein protects against renal ischaemia‐reperfusion injury in rats

Abstract: Our experiment suggested that a single dose of glutamine could relieve renal ischaemia-reperfusion injury in rats in 24 h, and its mechanism may be associated with enhanced heat shock protein expression. This finding may provide a new alternative for protecting against clinical renal ischaemia-reperfusion injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
4
15
0
Order By: Relevance
“…Our data on apoptosis are in accordance with the study of Zhang et al (2009) showing that glutamine pretreatment in rats was effective in alleviating the injury and apoptosis after kidney warm ischemic process. The animal model and administration route described by Zhang et al (2009) were different from ours, because intravenous injection of glutamine 1 h before renal warm I/R injury was used.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Our data on apoptosis are in accordance with the study of Zhang et al (2009) showing that glutamine pretreatment in rats was effective in alleviating the injury and apoptosis after kidney warm ischemic process. The animal model and administration route described by Zhang et al (2009) were different from ours, because intravenous injection of glutamine 1 h before renal warm I/R injury was used.…”
Section: Discussionsupporting
confidence: 95%
“…The animal model and administration route described by Zhang et al (2009) were different from ours, because intravenous injection of glutamine 1 h before renal warm I/R injury was used. Moreover, reperfusion periods chosen were 6 and 24 h, because HSP expression pattern was described.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, glutamine attenuates endotoxin-induced lung metabolic dysfunction [221] and reduces lung injury after sepsis, thus improving survival, by enhancing HSP70 expression [222,223]. Moreover, glutamine protects against renal ischemia-reperfusion injury [224]. This is because glutamine protects against cellular injury by increasing HSF1 function [225].…”
Section: Glutamine Metabolism and Its Importance For The Heat Shock Rmentioning
confidence: 99%
“…& Wischmeyer, P.E., 2008) in a process that is mediated, at least partially, by the increase in the flux through the hexosamine biosynthetic pathway (Hamiel et al, 2009). Also, it has been shown that a single dose of L-glutamine relieve renal ischaemia-reperfusion injury in rats in 24 h by a mechanism associated with enhanced HSP70 expression (Zhang et al, 2009). …”
Section: Intracellular Hsp70mentioning
confidence: 99%
“…Conversely, in LPS-endotoxemic rats, a single dose of L-glutamine, which is known to induce anti-inflammation via HSP70 expression (Wischmeyer et al, 2003;Singleton, K.D. & Wischmeyer, P.E., 2008;Hamiel et al, 2009;Zhang et al, 2009) has been shown to attenuate the release of TNF and IL-1 and to be associated with a significant www.intechopen.com decrease in mortality due to the attenuation of pro-inflammatory type 1 cytokines (Wischmeyer et al, 2001), whereas L-arginine-enriched diet limits plasma and muscle L-glutamine depletion in head-injured rats (Moinard et al, 2006). Remarkably, however, predominately Th1 (but not Th2) cell responses require the presence of optimal concentrations of L-glutamine (Chang et al, 1999).…”
Section: Participation Of L-arginine/l-glutamine Coupling In Diabetesmentioning
confidence: 99%